Bridging the gap: understanding the perspective of healthcare professional students towards precision medicine in a Nigerian tertiary institution (a cross-sectional study) - Ezinwanne Jane Ugochukwu; Jennifer Chinwe Edom; Faith Olanrewaju Omotayo; Agatha Adaeze Amaechi; Chinedu Benneth Obetta; Chibueze Anosike; AbdulMuminu Isah; Chukwuemeka Michael Ubaka (BMC Medical Education)
Abstract Background Individuals often respond differently to medications, giving rise to the field of precision medicine (PM), which focuses on tailoring treatments to individual genetic, environmental, and lifestyle factors. This study examined the level of comfort healthcare professional students have with their knowledge of precision medicine, alongside their attitudes and perceptions toward precision medicine, at a tertiary institution in Nigeria. Methods A cross-sectional questionnaire-based study was conducted among healthcare professional students (400–600 level) at the University of Nigeria Nsukka between January and March 2024. The data were analyzed via IBM Statistical Product and Service Solutions (SPSS) for Windows version 27. Descriptive analyses (frequency, percentage, mean, and standard deviation) and chi-square tests were used to summarize and compare the variables. Statistical significance was set at p < 0.05. Results A total of 431 healthcare professional students participated in this study. Fewer than half (n = 200, 46.4%) were pharmacy students, and the majority were within the age range of 21–25 years (n = 288, 66.8%). Nearly half (n = 206, 47.8%) reported having information about precision medicine from the internet, and the majority (n = 341, 79.1%) expressed having an interest in a career involving research in precision medicine. More than half of the students (n = 240, 55.7%) were comfortable with their knowledge of precision medicine and had favourable attitudes (n = 236, 54.8%). Additionally, more than half had positive perceptions of ethical concerns (n = 216, 50.1%) and education in precision medicine (n = 239, 55.5%). Gender, age, department, level of study, awareness of PM, and interest in a career involving research were significantly associated with students’ knowledge, attitudes, and perceptions of precision medicine (p < 0.001). Conclusion Healthcare professional students were comfortable with their knowledge of PM and, in addition, had favourable attitudes and positive perceptions toward the use of precision medicine.